Investigating Design of Semantic Based on Kain Punca Potong (KPP) Weaving Design: A Content Analysis - Ahmad, Nani Hartina; Shaari, Nazlina; Mohd Ali, Noor Azizi; Abd Latif, Muhammad Pauzi (International Journal of Psychosocial Rehabilitation, 2020)
The art of fabric design is no stranger to a society’s culture and art. Each masterpiece is a testament to its own meaning and philosophy that supplied insights and substance to human lives. Woefully, the presence and knowledge of each symbols and signs in fabric pattern design is now lost to the society. The semantic approach in fabric pattern production especially for kain punca potong is highly regretful, where the cloth’s pattern design was not carefully studied. The purpose of this study is to conduct an in-depth semantic explanation investigation, where the primary capacity of the images is to pass on specific messages if we somehow happened to think about the motif and pattern structure, materials, color, and different factors as the fundamental images to contemplate. This paper discusses the semantic approach in Kain Punca Potong (KPP) weaving design and content related to the functions of fabric formsymbols and meaning to provide several practical design cases as references. This study uses qualitative summative content analysis as its study design. The researchers analyzed watchwords identified with a situation of a semantic approach in this study. Articles chose to be analyzed in this study were published reporting the design semantic approach in fabric.